An analysis of ear discharge and antimicrobial sensitivity to the bacteria used in its treatment - Vaghela, Mukund M.; Doshi, Hiren; Rajput, Sneha (International Journal of Research in Medical Sciences, 2017)
Background: Children are unique population with distinct development and physiological differences from adults, clinical trials in children are essential to develop age-specific, empirically – verified therapies and interventions to determine and improve the best medical treatment available. The aim of this study was to find out the appropriateness and accuracy of the dose of drugs prescribed and compares it with standard dose. Methods: Total 400 prescriptions were collected from the OPD of the paediatrics of Shree Krishna Hospital, Karamsad. Calculation of standard total daily dose for each drug was done by using Clark’s formula and was compared with that of prescribed dose of that particular drug. Results: Total 1042 drugs were prescribed. Among antibiotics (22%) statistically significant difference in the prescribed and standard total daily dose was observed with cefexime [t-value 28.6>1.96 for 95% confidence interval] and metronidazole [t-value2.03>1.96 for 95% confidence interval], NSAIDs (31%), Paracetamol [t-value11.14>1.96 for 95% confidence interval] and antihistaminics (22%), phenylephrine [t-value7.1>1.96 for 95% confidence interval], cetrizine [t-value2.4>2.00 for 95% confidence interval]. Conclusions: Results show that prescribed doses of commonly used drugs were higher than the standard dose. This is directly related to the occurrence and severity of adverse drug reactions.